1
$\begingroup$

Gronwall's theorem is given as follows:

Assume that for $t_0\leq t \leq t_0 + a$, with $a$ a positive constant, we have the estimate $$\phi(t)\leq \delta_1\int_{t_0}^t\psi(s)\phi(s)ds + \delta_3\,\,\,\,\,(1.4)$$ in which, for $t_0\leq t \leq t_0 + a$, $\phi(t)$ and $\psi(t)$ are continuous functions, $\phi(t) \geq 0$ and $\psi(t)\geq 0$; $\delta_1$ and $\delta_3$ are positive constants. Then we have for $t_0\leq t\leq t_0 + a$ $$\phi(t) \leq \delta_3e^{\delta_1\int_{t_0}^t\psi(s)ds}$$

In my book the following proof of this theorem is proof is given:

From the estimate $(1.4)$ we derive $$\dfrac{\phi(t)}{\delta_1\int_{t_0}^t\psi(\tau)\phi(\tau)d\tau + \delta_3}\leq 1$$ multiplication with $\delta_1\psi(t)$ and integration yields $$\int_{t_0}^t\dfrac{\delta_1\psi(s)\phi(s)ds}{\delta_1\int_{t_0}^t\psi(\tau)\phi(\tau)d\tau + \delta_3}\leq \delta_1\int_{t_0}^t\psi(s)ds$$ so that $$\ln(\delta_1\int_{t_0}^t\psi(s)\phi(s)ds + \delta_3) - \ln\delta_3\leq \delta_1\int_{t_0}^t\psi(s)ds$$ which produces $$\delta_1\int_{t_0}^t\psi(s)\phi(s)ds + \delta_3 \leq \delta_3 e^{\delta_1\int_{t_0}^t\psi(s)ds}$$ Applying the estimate $(1.4)$ again, but now to the lefthand side, yields the required inequality.

Question: How does the step from $$\int_{t_0}^t\dfrac{\delta_1\psi(s)\phi(s)ds}{\delta_1\int_{t_0}^t\psi(\tau)\phi(\tau)d\tau + \delta_3}\leq \delta_1\int_{t_0}^t\psi(s)ds$$ to $$\ln(\delta_1\int_{t_0}^t\psi(s)\phi(s)ds + \delta_3) - \ln\delta_3\leq \delta_1\int_{t_0}^t\psi(s)ds$$ work? I think I understand the rest of the proof but I can't figure out the above step.

Thanks!

$\endgroup$
  • 1
    $\begingroup$ You should correct notation inside the integral, the lower integral's upper limit is $s$. I try to correct it but I'm not allowed. $\endgroup$ – Ernesto Iglesias Feb 19 '18 at 16:09
2
$\begingroup$

Ok, the thing is simple: think of the function $$F(t)=\delta_1\int_{t_0}^t\psi(\tau)\phi(\tau)d\tau + \delta_3,$$ it is in $C^1$ and $F'(t)=\delta_1\psi(t)\phi(t)$.

Then you just have to integrate $$\int_{t_0}^t\dfrac{F'(s)ds}{F(s)}=\int_{t_0}^t\dfrac{dF(s)}{F(s)},$$ and this is possible to do by variables change whenever $F(s)>0$, but that is guaranteed because $\psi(t),\phi(t),\delta_1,\delta_3$ are all positive and $t\geq{t_0}$.

Note: there are other proofs for Grönwall-Bellman's inequality, you may want to check the other ones (even Wikipedia have it's own).

$\endgroup$
0
$\begingroup$

It seems to me that the integration has been performed, try differentitating $$I =\ln(\delta_1\int_{t_0}^t\psi(s)\phi(s)ds + \delta_3) - \ln\delta_3$$

Noting the use of a dummy variable $\tau$ once the differentiation of the integral is obtained.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.